2011
DOI: 10.1097/hnp.0b013e3181fe266c
|View full text |Cite
|
Sign up to set email alerts
|

Referrals to Health Care Chaplaincy by Head Nurses

Abstract: To determine in which situations head nurses refer patients to health care chaplains and to detect significant influential factors, 192 head nurses from 117 health care institutions in the German part of Switzerland were surveyed with regard to situations in which they refer to a chaplain. On average, head nurses refer "often" to a chaplain in their daily work in situations where patients are dying or need religious-spiritual service or support, but they refer only "rarely" to a chaplain in situations where pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 19 publications
1
2
0
Order By: Relevance
“…Those with previous positive experiences, more favorable attitudes, or an accurate understanding of R/S and chaplaincy services appeared more amenable to having R/S discussions with patients and making referrals to chaplaincy services. These findings are consistent with previous studies [ 41 ] and the substantial variability of use of chaplaincy services among clinical staff [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…Those with previous positive experiences, more favorable attitudes, or an accurate understanding of R/S and chaplaincy services appeared more amenable to having R/S discussions with patients and making referrals to chaplaincy services. These findings are consistent with previous studies [ 41 ] and the substantial variability of use of chaplaincy services among clinical staff [ 28 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…It is possible that religious respondents connected with or appreciated the pastoral practitioner’s visit more than other patients may have, or may have completed the survey because they value the notion of pastoral care. Studies have found “the more religious or spiritual a patient is, the more he/she appreciated religious interventions and talking about religious/spiritual issues” (Winter-Pfändler, Flannelly, & Morgenthaler, 2011, p. 158). In his study, using the same data collection instrument, VandeCreek (2004) came to similar conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Swiss nurses who were religious were more likely to make chaplain referrals (Winter‐Pfandler et al . ).…”
Section: Introductionmentioning
confidence: 97%